PENERAPAN MODEL PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI KELAS X MIPA SMA N 9 PEKANBARU - Noval, Suci Asnah Putria; Abdullah, Abdullah; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The research aims to improve student learning achievement on the subject of stoichiometry in class XI MIPA SMA N 9 Pekanbaru. This research was a experiment with randomized group pretest-posttes design. The sample of this study was X IPA 5 as experiment class and X IPA 6 as control class after being tested for normality and homogeneity tests. Normality test was performed using Liliefors test. The results of the Liliefors normality test obtained for all the data (material prerequisites, pretest, and posttest) normal distribution where Lmaks ≤ Ltabel. The results of the homogeneity test, of Fhitung<Ftabel (1,05 < 1,72 with α = 0.05, dk=70) which means that the samples have the same variance (homogeneous). Data analysis technique used was t-test, obtained thitung ≥ ttable (3,4978 > 1,67 with dk = 70 and α = 0.05) means that the application of Means Ends Analysis (MEA) learning model can improve the presensce of the student achievement with criteria for improvinghigh learning achievements which is 0,82 .Key Words: Means Ends Analysis (MEA), student achievement, stoiciometry.